Design and Implementation of an AI-Based Digital Media Literacy Training Platform for English Teaching - Tao, Zhang; Saadat, Uranus (Journal of Theory and Practice in Education and Innovation, 2025)
This study presents an Artificial Intelligence (AI)-driven platform designed to enhance digital media literacy in English language education. By integrating natural language processing (NLP), deep learning, and reinforcement learning algorithms, the platform dynamically assesses users’ competencies in information retrieval, critical analysis, and information integration. It employs multimodal data analysis to generate personalized training tasks and real-time feedback. Experimental results demonstrate robust performance under high concurrency, with significant improvements in users’ critical thinking and information synthesis skills.